THE STRATEGY OF DEVELOPING STUDENTS’ TRANSLATION SKILL THROUGH ANALYSIS TECHNIQUE OF MACHINE ASSISTED TRANSLATION (MAT) AND MANUAL TRANSLATION (MT) - Wawan Tarwana; Iskhak Said (Universitas Galuh, 2022)
Machine-Assisted Translation (MAT) is a sophisticated intellectual technology made by man as a means of instant translation. One of them is Google Translate. This research is a case study with a qualitative approach. This research is to find out the following questions. 1) about the implementation of teaching techniques by applying MAT and MT analysis in the Translation course; 2) about perceptions of students of learning techniques using MAT and MT analysis in the Translation course; and 3) about the strategy of students in doing MT. The research data collection techniques were obtained from classroom observations, interviews with lecturers on Translation subjects, and documents from the results of student translations. All of these were conducted online because Covid had not passed. The object of his research was a lecturer in the Translation subject and 10 students from the Translation class. The data analysis technique used the data credibility test through the triangulation of techniques and sources. The result and the finding of this study are that the lecturer implements the MAT and MT analysis in the translation course with various stages. Meanwhile, students have the perception that the translation technique with the MAT and MT analysis strategy is very beneficial for their translation results. The strategy carried out by students in translating is using MAT and MT analysis in addition to using special translation techniques.